Psycho-oncology practice: Interventions regarding the emotional vulnerability of cancer patients - Yasin, Beatriz Garcia Abd; Silva , Dayane Ferreira da; Chaves , Jaqueline Barros; Abreu , João Pedro Carvalho de; Ortiz , Lygia Patrícia Galhardo (Seven Editora, 2023)
Psycho-Oncology is a field of psychology that acts in psychological care providing the development, treatment and rehabilitation of cancer patients, aiming to soften the processes and coping with the disease, both of patients and for family members and staff, so the objective of this study was to understand the practice of hospital psychology in the oncology service, and the psychologist’s interventions for the patient in emotional vulnerability to cope with the disease, thus, the literature review was used as a methodology, through searches on the academic Google platform and library of the Unigran Capital University Center, from 2000 to 2020. The results obtained were that the psychologist’s performance in psycho-oncology is to promote a better quality of life in cancer patients and also to promote awareness, change of thinking, welcoming, group exchanges, with the subjectivity of each patient. Where he found that the important thing is not to promote forms of intervention but to promote better quality of life of the patient, so that he has a better adherence to treatment. It was concluded that the psychologist in oncology is of paramount importance due to its form of reception, intervention, humanization and care of the patient, his family and the team. Promoting a better quality of life, whether in the healing or palliative process. DOI:https://doi.org/10.56238/ptoketheeducati-084